Young carers in Germany: to live on as normal as possible - a grounded theory study - Schnepp Wilfried; Metzing-Blau Sabine (BMC, 2008)
Abstract Background In contrast to a growing body of research on the situation of adult family care givers, in Germany hardly anything is known about the situation of children and teenagers who are involved in the care of their relatives. Methods In this Grounded Theory study 81 semi structured interviews have been carried out with children and their parents in 34 families, in which one member is chronically ill. 41 children and 41 parents participated and the sample is heterogeneous and diverse. Results On the one hand, there is the phenomenon 'keeping the family together", which describes how families themselves cope with the chronic illness and also, which tasks to what extent are being shifted and redistributed within the family in order to manage daily life. Influencing factors, the children's motives as well as the impact on the children also belong to this phenomenon. The second phenomenon 'to live a normal course of life' describes concrete wishes and expectations of support for the family to manage the hindered daily life. These two phenomena linked together constitute the 'model of experience and construction of familial care, in which children take over an active role'. Conclusion It will be discussed, that the more families are in dire need of support, the more their distress becomes invisible, furthermore, that management of chronic illness is a process, in which the entire family is involved, and thus needs to be considered, and finally, that young carer's relief is not possible without relief of their parents.